2007
DOI: 10.1016/j.nbd.2007.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-specific heme oxygenase-1 hyperexpression attenuates heme-mediated oxidative injury

Abstract: In prior studies, we have observed that HO activity protects astrocytes from heme-mediated injury, but paradoxically increases neuronal injury. In this study, we tested the hypothesis that an adenovirus encoding the human HO-1 gene driven by an enhanced glial fibrillary acidic protein promoter (Ad-GFAP-HO-1) would increase HO-1 expression selectively in astrocytes, and provide cytoprotection. Treatment with 100 MOI Ad-GFAP-HO-1 for 24h resulted in HO-1 expression that was 6.4-fold higher in cultured primary as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…11 Even HO activity protects astrocytes from heme-mediated injury, but paradoxically increases neuronal injury. 13 However, in our study, it is hard to tell the protective or harmful effects of serum HO-1 to our patients.…”
Section: Discussionmentioning
confidence: 63%
“…11 Even HO activity protects astrocytes from heme-mediated injury, but paradoxically increases neuronal injury. 13 However, in our study, it is hard to tell the protective or harmful effects of serum HO-1 to our patients.…”
Section: Discussionmentioning
confidence: 63%
“…39) In addition, many studies have identified the protective role of HO-1 induction in several different cells including macrophages, bovine aortic endothelial cells, and glia cells, against inflammation and oxidative injury. [40][41][42] This is despite the finding that the HO-1 promotor is highly promiscuous, since HO-1 is also inducible in response to a wide variety of stressors such as oxidative stress, heavy metals, UV radiation, and inflammation. 43) We observed that HO-1 expression in response to eupatilin was weaker in EEC at higher passage numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of subjects with HO-1 (-413) A allele to respond strongly in terms of upregulating HO-1 may be an important endogenous protective factor; in fact, the HO-1 (-413) AA genotype was found to reduce the incidence of myocardial infarction and angina pectoris, probably due to its high HO-1 promoter activity in coronary vessels [10] . HO-1 overexpression provides protective effects to neurons [7] and astrocytes [8] against heme-mediated oxidative injury. In the AD brain, numerous neurons throughout the hippocampus and temporal cortex exhibit intense HO-1 immunoreactivity, with a robust colocalization of HO-1 to the neurons containing the pathogenic hyperphosphorylated tau in NFT [5,6] , indicating a possible upregulation of antioxidant defenses in response to a pro-oxidant environment within the brain of AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays an early role in tau phosphorylation and neurofibrillary tangle (NFT) formation: (1) hyperphosphorylation of tau is attributable to mitochondrial oxidative stress in mice that lack superoxide dismutase 2 [2] ; (2) oxidative stress activates several kinases that have been shown to be activated in AD and are capable of phosphorylating tau [3] ; (3) a naturally occurring product of lipid peroxidation, 4-hydroxynonenal, is a major factor for aggregation of hyperphosphorylated tau and NFT formation [4] . In the AD brain, accumulation of hyperphosphorylated tau in NFT is associated with the induction of heme oxygenase-1 (HO-1) [5,6] , a potent antioxidant that protects neurons [7] and astrocytes [8] against heme-mediated oxidative injury. One notable effect of HO-1 overexpression is that expression of tau protein is specifically suppressed [9] , suggesting that regulation of tau expression might depend on HO-1 activity.…”
mentioning
confidence: 99%